Asymptotic behavior of generalized quasiisometries at a point - Kovtonyuk, D. A.; Salimov, R. R. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We consider $Q$-homeomorphisms with respect to the $p$-modulus. An estimate for a measure of a ball image isobtained under such mappings and the asymptotic behavior at zero is investigated.